Comprehensive Analysis of Accessible Tourism and Its Case Study in Indonesia - DAMIASIH, Damiasih; PALESTHO, Andrea; RAKA, Anak Agung Gede; KURNIAWAN, Hari; PEBRIANI, Putri; SUHENDROYONO, Suhendroyono; GUNAWARMAN, Anak Agung Gede Raka; MAULIDIMAS, Putradji (Journal of Environmental Management and Tourism, 2022)
Tourism matter in Indonesia has promising potential to be developed as future tourism development. However, the development of tourism in Indonesia is often based on the concept of implementation that is only looking for profitable matters. This paper focuses on accessible tourism, which is based on how to meeting the need and fulfilling the rights of tourists with disabilities and to facilitate elderly tourists. We present a review from 50 related articles on accessible tourism and further it can be used as a reference in actualising accessible tourism for tourists with disabilities and elderly tourists. In addition to defining the problem of accessible tourism in Indonesia today, we also present scenarios that are processed from thoughts based on recent sources which can be used as a reference for realizing accessible tourism, begin from developing in tourism objects, facilities, and human resources.